NMR, Novel Pharmacological and In Silico Docking Studies of Oxyacanthine and Tetrandrine: Bisbenzylisoquinoline Alkaloids Isolated from Berberis glaucocarpa Roots - Muhammad Alamzeb; Muhammad Omer; Mamoon Ur-Rashid; Muslim Raza; Saqib Ali; Behramand Khan; Asad Ullah (Journal of Analytical Methods in Chemistry)
Urease enzyme is responsible for gastric cancer, peptic ulcer, hepatic coma, and urinary stones in millions of people across the world. So, there is a strong need to develop new and safe antiurease drugs, particularly from natural sources. In search for new and effective drugs from natural sources bioassay-guided fractionation and isolation of Berberis glaucocarpa Stapf roots bark resulted in the isolation and characterization, on the basis of 1D and 2D NMR data, of two bisbenzylisoquinoline alkaloids, oxyacanthine (1) and tetrandrine (2), followed by urease inhibition studies. Crude extract, all the subfractions and the isolated compounds 1 and 2 displayed excellent urease enzyme inhibition properties in vitro. The antiurease nature and possible mode of action for compounds 1 and 2 were verified and explained through their molecular docking studies against jack-bean urease enzyme. Half-maximum inhibitory concentration (IC50) was calculated for compounds 1 and 2. The IC50 value was found to be 6.35 and 5.51 µg/mL for compounds 1 and 2, respectively. Both compounds 1 and 2 have minimal cytotoxicity against THP-1 monocytic cells.